(untitled) (The International Journal for Scientific Research, 2025)
This research aimed to evaluate the effects of fortifying oat flour with different proportions of germinated oats and vital gluten on its functional properties for producing functional oat bread with acceptable sensory qualities. First, the oat grains were germinated for 72 h and the germinated grains were dried at 40°C. Then, they were ground to obtain germinated oat flour. Vital gluten was extracted from the white flour manually and dried at 40°C. Then, the dry gluten was ground to obtain vital gluten powder. Three oat flour samples were prepared. They contained three different proportions of germinated oats (4, 24 and 44%) with a fixed value of vital gluten. The functional properties of the samples were studied, which included water and oil binding, solubility, swelling power, and foaming ability to determine the best level of germinated oats. This was followed by studying the effects of adding vital gluten in different values (6, 12 and 18%) to oat flour on its functional properties with a fixed value of germinated oats. The best proportion of germinated oats and vital gluten on the dough volume was also studied. The results showed that the addition of 4% germinated oats and 6% vital gluten achieved the best results of functional properties in terms of recording the highest swelling power, water binding, foaming ability and dough volume.